2007
DOI: 10.1007/s11248-007-9138-3
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic maize plants expressing a fungal phytase gene

Abstract: Maize seeds are the major ingredient of commercial pig and poultry feed. Phosphorus in maize seeds exists predominantly in the form of phytate. Phytate phosphorus is not available to monogastric animals and phosphate supplementation is required for optimal animal growth. Undigested phytate in animal manure is considered a major source of phosphorus pollution to the environment from agricultural production. Microbial phytase produced by fermentation as a feed additive is widely used to manage the nutritional an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
117
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(121 citation statements)
references
References 42 publications
2
117
0
Order By: Relevance
“…A thermotolerant phytase gene from Aspergillus has been used to alter phytic acid in maize, rice, and soybean (Table 3.10 ). For example, transgenic maize containing phyA2 gene showed a very high phytase activity (1791-2502 Unit kg À1 seed) and reduced phytic acid compared to WT (Chen et al 2008). Meanwhile, a MRP ATP-binding cassette transporter is highly expressed in embryo, and by silencing expression of this transporter, Shi et al (2007) produced transgenic maize low in seed phytate but high in Pi.…”
Section: Enhancing Seed Iron Zinc and B-carotene Using Transgementioning
confidence: 99%
“…A thermotolerant phytase gene from Aspergillus has been used to alter phytic acid in maize, rice, and soybean (Table 3.10 ). For example, transgenic maize containing phyA2 gene showed a very high phytase activity (1791-2502 Unit kg À1 seed) and reduced phytic acid compared to WT (Chen et al 2008). Meanwhile, a MRP ATP-binding cassette transporter is highly expressed in embryo, and by silencing expression of this transporter, Shi et al (2007) produced transgenic maize low in seed phytate but high in Pi.…”
Section: Enhancing Seed Iron Zinc and B-carotene Using Transgementioning
confidence: 99%
“…The data indicated that leaves of transgenic plant leaves remained green, while leaves of control plants turned and became necrotic yellow, which indicating resistance and sensitivity to the herbicide, respectively. In other studies of the T2 generation it has been found that transgenic plants can express different responses to the herbicide, for example only 48 out of 65 transgenic seedlings of maize remained Basta resistant (Chen et al, 2008). Also for 130 explants in tobacco after selection with Basta herbicide subsequently only81 plants were Basta tolerant (62.30%) (Soliman et al, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…Herbicide leaf painting assays: In order to evaluate the expression of bar gene, non-transformed (control) and putative transformed grape leaves were painted according to Chen et al (2008) with BASTA herbicide (a proprietary herbicide containing bialaphos) at a concentration of 2.0 g L -1…”
Section: Detection Of Transgenic Plantsmentioning
confidence: 99%
“…The strategy of overexpressing ferritin received attention because plant ferritins have shown absorption as high as ferrous sulfate in rat models 16 and in humans. 17 It is now understood that ferritin is degraded during digestion and iron associated with the protein will enter the common nonheme iron pool, making it susceptible to phytate inhibition. 43 Unlike ferritin, hemoglobin has a unique uptake pathway and transport mechanisms, 44 and the heme pyrrole is protective against the inhibitory effects of phytate and other nonheme iron inhibitors.…”
Section: ■ Discussionmentioning
confidence: 99%